ANALISIS SEMIOTIKA FERDINAN DE SAUSSURE DALAM NOVEL GARIS WAKTU KARYA FIERSA BESARI - Roita Sinaga (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this research is to analyze the semiotics of Ferdinand De Saussure in the novel Garis Waktu by Fiersa Besari. The writer needs to study the semiotics in the novel Garis Waktu from the perspective of Ferdinand De Saussure to enrich the literary appreciation of this novel, especially since no other researcher has analyzed this part. Even though this novel is very well known among the public. The type of research used in this research is descriptive research, which aims to collect information about the current state of a phenomenon. The data in this study were sourced from the novel Garis Waktu by Fiersa Besari. The writer analyzes the semiotics of Ferdinand De Saussure in the novel Garis Waktu by Fiersa Besari. Data in the research context can be in the form of words, sentences or real situations and conditions related to the research being conducted. The data used in this study are phrases, sentences containing signifiers and signifieds in this novel. The results of this study indicate that there are sentences containing signifiers and signifieds in the novel Garis Waktu by Fiersa Besari.